Validation of the Smart Leadership Model among Managers of Farhangian University - Pouraghajan Hoseini, Seyedeh Mahsa; Taghvaee Yazdi, Maryam; Enayati, Taraneh (Assessment and Practice in Educational Sciences, 2026)
The present study was conducted with the aim of examining and identifying the validation of the Smart Leadership Model among managers of Farhangian University. The research method is applied in terms of purpose and employs a mixed exploratory design combining qualitative and quantitative data. Accordingly, the qualitative phase utilized content analysis for model development, while the quantitative phase adopted a descriptive–survey method for model validation. The qualitative population included all expert policymakers, managers, and educational planners of Farhangian University in Mazandaran Province. The quantitative population consisted of all managers and faculty members of Farhangian University in Mazandaran Province (located in the cities of Sari, Qaemshahr, Babol, Amol, and Nowshahr), comprising 150 managers and 480 faculty members. The sample in the qualitative phase included 10 participants selected based on the principle of theoretical saturation, and in the quantitative phase, 239 individuals were selected using Cochran’s formula through multistage cluster and stratified sampling. Data collection methods consisted of semi-structured interviews in the qualitative phase and a researcher-made questionnaire in the quantitative phase. Face, content, and construct validity, as well as reliability, were confirmed using Cronbach’s alpha coefficient and composite reliability. For data analysis, open and axial coding using MAXQDA software were applied in the qualitative phase, and structural equation modeling using PLS software was employed in the quantitative phase. The findings indicated that 48 indicators and 9 components were identified and analyzed for Smart Leadership.